2020
DOI: 10.1055/s-0040-1709672
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus in Pregnancy: A Systematic Review of the Literature

Abstract: Objective The aim of this study was to systematically review the literature to summarize recent demographic characteristics of hepatitis C virus (HCV) infection during pregnancy and the efficacy of risk-based versus universal screening. Study Design PubMed, EMBASE, and Cochrane Library were searched to identify relevant studies. Studies that recognized hepatitis C as a primary or secondary outcome, with pregnant women as the population and written in English, were included. Studies were excluded if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Risk-based screening of pregnant women in other countries follows differing protocols with respect to risk groups (e.g. some include women with an IDU history while others also extend to those with a sexual partner who inject drugs; other protocols include women from high-prevalence areas) [ 20 ]. A few studies have compared risk-based with universal screening, and have shown that women with a known risk factor, such as injecting drug use, may not be screened under current guidelines [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk-based screening of pregnant women in other countries follows differing protocols with respect to risk groups (e.g. some include women with an IDU history while others also extend to those with a sexual partner who inject drugs; other protocols include women from high-prevalence areas) [ 20 ]. A few studies have compared risk-based with universal screening, and have shown that women with a known risk factor, such as injecting drug use, may not be screened under current guidelines [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…some include women with an IDU history while others also extend to those with a sexual partner who inject drugs; other protocols include women from high-prevalence areas) [ 20 ]. A few studies have compared risk-based with universal screening, and have shown that women with a known risk factor, such as injecting drug use, may not be screened under current guidelines [ 20 ]. In England, although coverage of HCV testing among high-risk pregnant women is unknown, testing of migrant groups in primary care settings is variable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation